2010
DOI: 10.1016/j.cma.2010.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Reuleaux plasticity: Analytical backward Euler stress integration and consistent tangent

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…Due to symmetry only half of the 10m by 5m domain was discretised using 135 eight-noded quadrilateral finite elements with reduced four-point integration (as shown on the right of Figure 9). The mesh used is that same as that adopted by [34] and [7]. The material was assumed to be weightless and had a Young's modulus of E = 100MPa and a Poisson's ratio of ν = 0.3.…”
Section: Rigid Footingmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to symmetry only half of the 10m by 5m domain was discretised using 135 eight-noded quadrilateral finite elements with reduced four-point integration (as shown on the right of Figure 9). The mesh used is that same as that adopted by [34] and [7]. The material was assumed to be weightless and had a Young's modulus of E = 100MPa and a Poisson's ratio of ν = 0.3.…”
Section: Rigid Footingmentioning
confidence: 99%
“…See [9,29] for a detailed review of implicit methods for computational plasticity. Several other implicit stress integration procedures have been proposed over the last 50 years, including [14-16, 25, 30], in addition to some analytical integration methods [6,7,10]. The major advantage of these implicit approaches is that the consistency conditions are enforced at the updated stress state.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ignoring the dependence of constitutive relations on the third invariant of stress can lead to significant overestimation of the stiffness in geotechnical analyses [15,18,34]. A number of Lode angle dependencies have been proposed in the literature, for example [1,2,31,32,40,44].…”
Section: Lode Angle Dependencymentioning
confidence: 99%
“…Ignoring the dependence of constitutive relations on the third invariant of stress can lead to significant over-estimation of the stiffness in geotechnical analyses (Coombs et al (2010); de Souza Neto et al (2008); Potts and Zdravkoić (2001)). A number of LADs have been proposed in the literature (for example see Bardet (1990); Bhowmik and Long (1990); Coombs et al (2010); Lade and Duncan (1973); Matsuoka and Nakai (1974); Shield (1955); Willam and Warnke (1974)).…”
Section: Rate Of Dissipationmentioning
confidence: 99%
“…A number of LADs have been proposed in the literature (for example see Bardet (1990); Bhowmik and Long (1990); Coombs et al (2010); Lade and Duncan (1973); Matsuoka and Nakai (1974); Shield (1955); Willam and Warnke (1974)). Collins (2003) combined the Matsuoka-Nakai (M-N) yield condition with the CS cone by re-defining q in the spatially mobilised plane (see Matsuoka and Nakai (1974)).…”
Section: Rate Of Dissipationmentioning
confidence: 99%